An extended, 2.4-ka long record of western Pacific tsunamis and pumice rafts in northern Taiwan: Tsunami recurrence, pumice sources, and drifting routes. (1st April 2022) - Yu, Neng-Ti; Yen, Jiun-Yee; Yen, I-Chin; Chu, Mei-Fei
Abstract: Encircled by arcs and trenches, the western Pacific region of the Philippine Sea is exposed to trans-oceanic tsunamis and pumice rafts. However, shortage of extended archive has limited our knowledge of tsunami recurrence, pumice sources, and drifting routes. This study identifies a backshore colluvium with three new pumice gravel layers in northern Taiwan, stratigraphically below four previously reported pumice-bearing paleotsunami deposits from the last millennium. The new layers are attributed to tsunamis, based on foreshore-derived sediments, facies characteristics reflecting suspension-rich turbulent flow process, supratidal locations exceeding typhoon surge heights, and mismatched super typhoon occurrences. The tsunami record therefore extends in duration from 1.0 to 2.4 ka with an increase in event number from four to seven, which unfolds new time intervals, stretches the recurrence from 100–400 to 100–800 years, and indicates complicated tsunami occurrences and sources in this region. Simultaneously, a stranded pumice archive is established by six of the seven paleotsunami deposits with abundant pumices rounded by grain-to-grain abrasion during drifting. The pumices consist of black, shoshonitic trachyte–trachyandesite grains and white, low-K dacite–rhyolite grains, indicating diverse sources and drifting routes. The unique alkali and adjoining subalkaline volcano provinces of the Izu-Bonin-Mariana Arc might have successively generated pumice rafts since 2.4 ka that embarked the Kuroshio counter and branch currents for northern Taiwan in a ∼2000-km-long course across the Philippine Sea. White rhyolite pumice domination is also present and comparable in composition to the southern Ryukyu pumice, indicating a ∼200 km-long northwest-bound route. Highlights: A prolonged record of western Pacific tsunamis and pumice rafts is established in northern Taiwan for the first time. Seven pumice-bearing tsunami deposits from 2.4 ka recurred at a 100–800-year interval. Compositional ties to the Izu-Bonin-Mariana Arc pumice rafts across the Philippine Sea are prominent. Pumice comparable to those from the adjacent southern Ryukyu Arc occasionally dominated.